Seismic Response and Vulnerability Assessment of Representative Low, Medium and High-rise Buildings in Patna, India. (June 2019) - Samanta, Avik; Swain, Arabinda
Abstract: The behavior of structures built on soft soil can be significantly different from the structures built on rocky soil. It is necessary to know the response of structures build on such soft soil conditions. Over the last few decades many researchers have studied merits and demerits of soil structure interaction (SSI). However the findings are contradictory in many aspects. Thus it may be necessary to assess vulnerability of structures founded on soft soil deposits. In this work, response and seismic vulnerability of representative low (3 storey), medium (6 storey) and high-rise (9 storey) reinforced concrete buildings in Patna, India are assessed. To obtain the seismic response of structures, representative reinforced concrete buildings with masonry infill walls are studied with and without SSI using SAP2000. It is found that consideration of SSI may provide underestimation of structural responses and vulnerability for the structures and site considered in this study.